DETERMINAN STRUKTUR MODAL DAN NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Yunita Yunita; Robiyanto Robiyanto (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
This study examines the influence of internal company factors such as profitability, company size, business risk, company growth rate and external factors of the company, namely market risk on the company's capital structure as an intervening variable that affects the value of the company. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the study period of 2013 to 2018 and a sample of 82 companies. This study found that profitability and company size factors have a significant influence on the company's capital structure, but business risk, growth rates, and market risk do not have a significant effect on capital structure. Then capital structure has a significant influence on firm value.